Argentinean Larrea Dry Extracts with Potential Use in Vaginal Candidiasis - Moreno, María Alejandra (2018)
Larrea divaricata (Ld), Larrea cuneifolia (Lc) and Larrea nitida (Ln) are shrubs occurring in Northwestern Argentina used in traditional medicine to treatfungal and bacterial infections and as anti-inflammatory. Antibacterial and antifungal activity of several Larrea species has been reported. However, theirpotential use in vaginal infections has been so far not assessed. The aim of this work was to determine the botanical difference between Larrea species, thechemical composition and the activity of Larrea dry extracts (DE) on Candida species isolated from vaginal infections and to assess their potential asantioxidant agents because infections are usually associated with oxidative processes. The main botanical difference between Larrea species resides in themorphology and shape of leaf, leaflets and stipules, presence or absence of mucron and rachis, percentage of coalescence of the leaflets. The position andabundance of the sclerenchymatic tissue at the mind vein and petiole transection allows the differentiation of the three species. The profile of phenoliccompounds in the Larrea DE was determined. HPLC-ESI-MS/MS analysis of DE allowed the identification of 2 flavonoids and 10 lignans. Trihydroxy-6,7´cyclolignan was found only in L. divaricata and dihydroxy-methoxy-epoxylignan in L. cuneifolia and L. nitida, nordihydroguaiaretic acid (NDGA) wasfound in the three species. All extracts showed antioxidant capacity. The DE showed to be effective against Candida albicans and non-albicans strains.According to our results, the local vaginal use of Larrea DE in the concentration range of MIC values for Candida species does not affect the Lactobacillusnormal vaginal microbiota. This work adds evidence to the potential use of Larrea DE as phytomedicine in vulvovaginal candidiasis with multiple effects,including antifungal and antioxidant activity.